Tuning the viscoelastic features required for 3D printing of PVC-acrylate copolymers obtained by single electron transfer-degenerative chain transfer living radical polymerization (SET-DTLRP) - M. I. Calafel; R. H. Aguirresarobe; N. Sadaba; M. Boix; J. I. Conde; B. Pascual; A. Santamaria (eXPRESS Polymer Letters)
Random poly (vinyl chloride-co-butyl acrylate) and poly (vinyl chloride-co-2-ethylhexyl acrylate copolymers obtained by single electron transfer-degenerative chain transfer living radical polymerization (SET- DTLRP) are investigated as potential candidates for 3D Printing. The analysis of the rheological implications of 3D Printing process allows establishing the basic viscoelastic conditions that the samples should fulfil to be printable, avoiding the ‘trial and error’ procedure. The effect of temperature and acrylates concentration on the rheological properties and 3D printing feasibility is contemplated. Eventually, thermal degradation is also considered. It is demonstrated that the copolymers which contain butyl acrylate comonomer, instead of 2-ethylhexyl acrylate, give raise to the best results. Although the study is carried out with PVCacrylate copolymers and a 3D printing device that possesses set up characteristics, it shows a way to work out sound strategies with other polymers and 3D printing machines.